SISTEM INFORMASI MANAJEMEN PENDIDIKAN KELUARGA DALAM ISLAM BERDASARKAN AL QUR’AN DAN HADIST - Mizanul Hasanah (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2020)
This study aims to covey to the public that the importance of management information systems for the development of Islamic education. Schools as forming the continuation of education in the family, because education is first and foremost obtained by children is in the family. No matter how good the role of the environment and school is still a family that has an important role in determining the character and mindset of the individual. Islam presents guidelines for humans to shape Islamic education. Islam has a primary source as an information-oriented communication tool that will be delivered to Muslims, namely the Qur’an and As-Sunnah (hadith). The Messenger of Allah was a hacker and a guide and example of how to apply the values contained in the Qur’an in real life. Comunication that has been built by the prophet, family and friends as a form of information about Islam whose guidelines are the Qur’an and the Hadith. So,   the overall goal of the form delivery of information in management must be a system that regulates include components, including the Prophet. All information relating to the religious life of Islam, the problems that exist in the life of all have governed in the Qur’an and Hadith.